Indian aesthetic dance and yoga improves mental health among caregivers of children with neurodevelopmental disorders: a randomized trial - Hegde, Jayashree R.; Melukote, Sridhar K.; Srinivasan, T. M.; Singh, Deepeshwar (International Journal Of Community Medicine And Public Health, 2020)
Background: This study aimed to assess the effects of Indian aesthetic dance (IAD) and yoga on psychological behavioral and mental health-related problems among the caregivers of children with neurodevelopmental disorders (NDDs). Methods: One hundred one caregiver participants were randomly allocated to either intervention of IAD or a structured yoga program or in a control group. The invention groups received supervised eight-weeks IAD or yoga training for 3 alternative days, 75 min each day. In total, 96 subjects completed the study with after high adherence of 95% to intervention sessions. Caregivers were assessed with self-rated primary measures including the Zarit burden scale (ZBS), depression, anxiety, and stress (DASS-21) scale; and secondary measures were revised caregiver’s appraisal scale (RCAS) and WHO Quality of Life WHOQOL (BREF) scale. The assessments were done at pre (1st day), mid (ENT of 4th week), and post (end of 8th week) of interventions. Results: Statistical analysis showed there was a significant reduction in scores of ZBS (p<0.001), DASS-21 (p<0.001), and significant improvement was found in the subscales of RCAS and WHOQOL (BREF) (p<0.001). Conclusions: The outcome of the study suggests that IAD and Yoga can be feasible interventions for alleviating symptoms of mental health-related issues among caregivers.